Color Schemes From Flowers - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how to take inspiration from nature to determine color scheme and decorations when designing a room. Includes small stylized illustrations, monotone photographs, and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Interior decoration; Dwellings--Remodeling